The predictors of post-partum depression in a tertiary centre - Unnisa, Sadiq; Lavanya, Poluri Seetha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The present study was undertaken to evaluate the association of different socio-demographic, obstetric and pregnancy outcome as predictor of PPD among the postnatal women during early puerperium and thus can be provided with special care. Objective was to evaluate the different predictors of post partum depression. Methods: A prospective study was conducted in the department of obstetrics and gynaecology, Yenepoya medical college hospital Mangalore. A total of 200 postnatal mothers in their 3rd - 7th postpartum day were interrogated using Edinburgh postnatal depression scale (EPDS). Socio-demographic factors like age, parity, literary, socio economic status, family structure, obstetric outcome was recorded. Results were statistically analyzed with chi-square test. Results: A prospective study was conducted in the Department of Obstetrics and Gynaecology, Yenepoya Medical College Hospital, Mangalore. A total of 200 postnatal mothers in their 3rd - 7th postpartum day were interrogated using Edinburgh postnatal depression scale (EPDS). Socio-demographic factors like age, parity, literary, socio economic status, family structure, obstetric outcome was recorded. Results were statistically analyzed with chi-square test. Conclusions: Risk of PPD is more with the birth of a female baby, women who had CS, low S.E status, unemployment could predict higher risk for PPD. PPD screening should be an integral part of postnatal care using E PDS routinely. A multidisciplinary approach including obstetrician and psychiatrists can be jointly care of the depressed mothers.